In Vitro Study of Isoflavones and Isoflavans as Potent Inhibitors of Human 12- and 15-Lipoxygenases - Sepulveda-Boza, S; Espinosa-Ferrada, V; Mascayano-Collado, C (2013)
In this study, we have investigated 16 isoflavone and isoflavan derivatives as potential inhibitors of human lipoxygenase (platelet 12-lipoxygenase, reticulocyte 15-lipoxygenase-1, and epithelial 15-lipoxygenase-2). The flavonoid baicalein, a known lipoxygenase inhibitor, was used as positive control. Four compounds, 6,7-dihydroxy-3?-chloroisoflavone (1c), 7-hydroxy-8-methyl-4?-chloroisoflavan (5a), 7,8-dihydroxy-4?-methylisoflavan (5b), and 7,8-dihydroxy-3?-methylisoflavan (5c), were effective inhibitors of 12-lipoxygenases and 15-lipoxygenase-1 with IC50 s <10 ?m, while 6,7-dihydroxy-4?-nitroisoflavone (1b) was a selective inhibitor of 12-lipoxygenases. Docking studies, antioxidant assays, and kinetic measurements were carried out for the three best inhibitors (1b, 5b, 5c). The results showed that a catechol group in ring A is critical for the antioxidant properties of these compounds, and probably essential for their inhibitory activity. Kinetic assays showed that compounds 1b, 5b, and 5c are competitive inhibitors with Ki values in the range of 0.3-3 ?m. © 2013 John Wiley & Sons A/S.